The Implementation of Eco-design Tools in Practice: A Case Study of PVC Windows - Denac, Matjaž (Študije primerov EPF: Razvoj, trajnost in inovacije v poslovni praksi 2024, 2024)
Managers face many challenges in the environmental management of their companies, including the development of greener products. Applying eco-design principles is a big step towards preventing environmental problems at source and, hence towards a more sustainable society. There are several tools available for the eco-design of products, which vary in complexity and can shed light on different aspects of product design. The most comprehensive eco-design tools consider the environmental impacts generated at each stage of the life cycle of products. This study demonstrates a systematic approach to introducing eco-design in the construction sector for professionals and stakeholders interested in greener product development. No prior knowledge of general design processes and related market aspects is required to understand the eco-design concept presented. The application of selected product eco-design methods is demonstrated in a PVC furniture manufacturing company. Using PVC windows as an example, this guide walks the reader through the stages of product eco-design, showing how the same environmental optimization tools can be applied to other building products.